2017
DOI: 10.14260/jemds/2017/183
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Haemoglobinopathies and Haemoglobin Variants Using High Performance Liquid Chromatography (Hplc) in a Teaching Hospital of Odisha

Abstract: BACKGROUND Thalassaemias and haemoglobinopathies are highly prevalent in India. Identification of these disorders is important for epidemiologic purposes and for prevention of thalassaemia major and clinically severe haemoglobinopathies. The use of high performance liquid chromatography (HPLC) as a screening method for detection of these groups of disorder is increasing in last two decades. The aim is to study of thalassaemias and haemoglobinopathies using high performance liquid chromatography as a diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The study by Alam et al [7], Shankar et al [12], and Jain et al [13] did not report the abnormal hemoglobins of Hb Q India, Hb J Meerut, Hb D Iran, Hb Lepore, and HPFH, respectively. Similarly, the studies by Alam et al [7], Raman et al [9], and Sarvaiya and Chauhan [10] have not reported the presence of Hb Q India, Hb J Meerut, and Hb D Iran.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The study by Alam et al [7], Shankar et al [12], and Jain et al [13] did not report the abnormal hemoglobins of Hb Q India, Hb J Meerut, Hb D Iran, Hb Lepore, and HPFH, respectively. Similarly, the studies by Alam et al [7], Raman et al [9], and Sarvaiya and Chauhan [10] have not reported the presence of Hb Q India, Hb J Meerut, and Hb D Iran.…”
Section: Discussionmentioning
confidence: 87%
“…The abnormal hemoglobin variants reported within the 14 studies and from this study for type and frequency are shown in Table 2. The commonest abnormal hemoglobin variant in all the studies was βTT and with a cumulative percentage of 42.6% [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The last reported variant in the Indian population was Hb D Iran, with a percentage of 0.02% [1,5,6].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations